Synthesis of Novel Benzofuran-Based Thiazole Hybrids and Investigation of Their Antioxidant and Anticholinesterase Activities - Kaya, Betül; Maryam, Zahra; Daoud, Nour El Huda; Bağcı, Emine Rana; Karakaya, Abdüllatif; Erçeti?n, Tu?ba; Çevik, Ulviye Acar (Society of Pharmaceutical Sciences of Ankara (FABAD), 2025)
In this study, a novel series of benzofuran derivatives (2a-2k) was synthesized, and the structures of the obtained compounds were elucidated by 1H NMR, 13C NMR, and HRMS spectra. The compounds were investigated for their anticholinesterase and antioxidant potentials. The ferrous ion chelating activity of the compound 2g at 50 ?M concentration was 68.25%, surpassing those of rutin and BHT (13.21% and 2.57%, respectively). Besides, according to the DPPH radical scavenging activity assay, compound 2g exhibited the most potent antioxidant activity with an IC50 value of 30.14 ± 0.005 ?M, when compared to standard gallic acid (IC50 29.48 ± 0.014 ?M). Furthermore, compounds 2d (10.33%) and 2i (20.17%) showed the highest inhibitory activity against AChE and BChE, respectively. Compound 2i exhibits important interactions with the active site of BChE, according to the in silico molecular docking study. Also, the in silico ADMET study revealed the desirable pharmacokinetic properties of compound 2i. Therefore, compounds 2g and 2i could be deemed as promising candidates for designing dual functional antioxidant and butyrylcholinesterase inhibitors in the management of Alzheimer’s disease. © 2025, Society of Pharmaceutical Sciences of Ankara (FABAD). All rights reserved.
Benzofuran Temelli Yeni Tiyazol Hibritlerinin Sentezi ve Antioksidan ve Antikolinesteraz Aktivitelerinin İncelenmesi
Keywords: Alzheimer’s disease; anticholinesterase; Benzofuran; DPPH assay; ferrous ion-chelating activity